2014
DOI: 10.7314/apjcp.2014.15.15.6339
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Rectal Cancer in Patients Aged 30 Years or Less in the Pakistani Population

Abstract: Background: The incidence of rectal cancer is increasing in younger age groups. Limited data is available regarding survival outcome in younger patients with conflicting results from western world. The goal of this study was to determine survival in patients with rectal cancer <30 years of age and compare it with their older counterparts in the Pakistani population. Materials and Methods: A retrospective chart review of patients operated for rectal adenocarcinoma between January 2005 and December 2010 was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our finding that CRC is the commonest GI cancer among YIs is supported by similar results found in other parts of the world including developed countries like United States, Europe, Canada, Australia and New Zealand where a sharp rise in such cases has been demonstrated 2‐7 . In Pakistan too, this trend has been noted in earlier studies and emphasis has been laid upon need for further research work and early age of screening to detect rectal cancers 15‐17 . A significant proportion of our patients with rectal cancers exhibited signet ring cell histology (SRCH).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our finding that CRC is the commonest GI cancer among YIs is supported by similar results found in other parts of the world including developed countries like United States, Europe, Canada, Australia and New Zealand where a sharp rise in such cases has been demonstrated 2‐7 . In Pakistan too, this trend has been noted in earlier studies and emphasis has been laid upon need for further research work and early age of screening to detect rectal cancers 15‐17 . A significant proportion of our patients with rectal cancers exhibited signet ring cell histology (SRCH).…”
Section: Discussionsupporting
confidence: 87%
“… 2 , 3 , 4 , 5 , 6 , 7 In Pakistan too, this trend has been noted in earlier studies and emphasis has been laid upon need for further research work and early age of screening to detect rectal cancers. 15 , 16 , 17 A significant proportion of our patients with rectal cancers exhibited signet ring cell histology (SRCH). Various studies done elsewhere in the world show that SRCH is more common in young than in old patients and may represent more advanced stage at presentation and worse prognosis compared with mucinous and non‐mucinous rectal adenocarcinomas.…”
Section: Discussionmentioning
confidence: 95%
“…Associated work up and planning has been discussed elsewhere (Akbar et al, 2014). The standard protocol was to administer preoperative CRT in T3/T4 and/or clinically node positive tumors.…”
Section: Methodsmentioning
confidence: 99%
“…A few sporadic studies have emerged over the years suggesting this fact. In a small series, this percentage was reported to be 26.3% in rectal carcinoma patients below 30 years of age group [11]. Another study reported the ratio of under age 40 to over age 40 patients in colorectal cancer to be 0.3 [12].…”
Section: Introductionmentioning
confidence: 99%